Associations of Exercise Habits and Circulatory Dynamics with Peripheral Lower Limb Body Composition in Healthy Community-dwelling Older Individuals - Kogo, Haruki; Yamashita, Yuh; Murata, Jun (Journal of Community Medicine and Health Solutions, 2022)
We investigated the associations between circulatory dynamics and Body Composition (BC) of the peripheral lower limbs with Exercise Habits (EHs). We surveyed the EHs of 34 healthy older adults (6 men, 28 women) and measured their BC and skin perfusion (SP). SP did not correlate significantly with any other variable. Participants with established EHs had a lower body weight and Fat Tissue thickness (Fat-T) than those without. Multiple logistic regressions with the presence or absence of an EH as the dependent variable and BC values as the independent variables established Fat-T as a significant variable. Sex was independently associated with soleus muscle thickness, Fat-T, Bone Density (BD), and leg segmental water. Age was independently associated with Fat-T and BD, and body mass index was associated with Fat-T. EHs were not independently associated with any of the BC measurements. Physical characteristics and EHs have minimal influence on peripheral circulatory dynamics.